(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In our case study, we show the organization of the project of installing new production plant with an emphasis on the release of human creative potential. Purpose: In the case study, we wanted to show what approaches a leader is available and what is important to optimize the climate within the project team in order to get the most out of each member of the project team Method: When writing articles we systematically reviewed the achievements of eminent experts on the surveyed area. We also used the method of participant observation. The author is head of the project team. Results: The result of the study is to set project organization with clearly defined values, vision, objectives and mission. Organization: Demonstrate the benefits which the organization received, the optimal exploitation of human potential. Society: Optimal implementation of projects beneficial effect on the development of society. Originality: In practice, it is a rare case that the members of the project team also later users and holders of regular production. We present the advantages of such an approach. Limitations/Future Research: The study was limited to only one organization. In the future it would be good to do a similar study in other similar company and to compare the results obtained with our own.